Ecological Assessment of Everyday Executive Functioning at Home and at School Following Childhood Traumatic Brain Injury Using the BRIEF Questionnaire. Issue 6 (November 2017) - Chevignard, Mathilde; Kerrouche, Bernadette; Krasny-Pacini, Agata; Mariller, Aude; Pineau-Chardon, Emmanuelle; Notteghem, Pauline; Prodhomme, Julie; Le Gall, Didier; Roulin, Jean-Luc; Fournet, Nathalie; Roy, Arnaud
Abstract : Objectives: To describe dysexecutive symptoms in children with traumatic brain injury (TBI) using the Behavior Rating Inventory of Executive Function (BRIEF); to compare parent- and teacher-ratings, to analyze the differential impairment in the BRIEF subscales, and factors influencing outcome. Participants: Children aged 5 to 18 years 11 months, referred to a rehabilitation department following TBI. Outcome Measures: Parent- and teacher reports of the BRIEF. Results: A total of 194 patients participated in the study: mild ( n = 13), moderate ( n = 12), severe ( n = 169); mean 4.92 (standard deviation = 3.94) years post-injury. According to parent ratings ( n = 193), all BRIEF subscales and indices were significantly elevated (23.8%–48% in the clinical range). The Working Memory subscale score was significantly higher than all other subscales. Results of teacher ratings ( n = 28) indicated similar significantly elevated scores in all subscales (39.3%–57.2% in the clinical range). No significant difference was found between parent and teacher ratings, which were significantly correlated. Regression analyses indicated that, in children with severe TBI, parental BRIEF overall and metacognition indices were significantly predicted by younger age at injury and older age at assessment, whereas no significant predictor of behavioral regulation index was identified. Discussion and Conclusion: This study highlights significant executive dysfunction in everyday life several years after childhood TBI, evident in home and school environments.